ASSA13-03-55 MicroRNA-31 Regulate Phenotypic Modulation of Human Vascular Smooth Muscle Cell Via Its Target Gene CREG. (29th April 2013) - Jie, Wang; Chenghui, Yan; Jie, Tao; Chengfei, Peng; Xiaoxiang, Tian; Yaling, Han
Abstract : Background and Objective: Cellular repressor of E1A-stimulated genes (CREG) plays an important role in phenotypic modulation of VSMCs, but the mechanism of its upstream signalling regulation is not clear. Recently, microRNAs (miRNA) have been found to play a critical role in cell differentiation and proliferation, suggesting that miRNA may be an upstream regulator of CREG. Thus, we aimed to investigate which miRNA bind to CREG directly and involved in CREG-mediated effect on VSMCs phenotypic modulation. Methods: Human VSMCs were stimulated by platelet derived growth factor (PDGF) and serum starvation to establish phenotypic modulation model. Expression of CREG and VSMC differentiation marker genes in different phenotypic VSMCs were determined by Western blot. Computational analysis has suggested that miR-31 is able to bind to CREG mRNA 3′-UTR. To find the miRNA which has a negative relationship with CREG, CREG and miR-31 expressions were determined by qRT-PCR in VSMCs with different phenotype. To overexpress and knockdown miRNA expression, miRNA mimic and inhibitor were used. SM α-actin and CREG expressions were analysed by Western blot and qRT-PCR. To identify miR-31 can bind to CREG directly, luciferase expression of a firefly luciferase reporter construct containing CREG mRNA 3′-UTR was measured by using a dual luciferase reporter system. At last, CREG was knocked down by its shRNA in VSMCs and miRNA inhibitor was transfected into CREG deficient cells, SM α-actin expression were determined by Western blot. Results: In cultured VSMCs, VSMC differentiation marker genes and CREG expressions were downregulated in differentiated VSMCs and upregulated in proliferative cells. As expected, miR-31 and CREG have a negative relationship at protein and mRNA level in VSMCs with different phenotype. Furthermore, gain-of-function and loss-of-function showed that SM α-actin and CREG expressions are suppressed by miR-31 mimic and are increased by miR-31 inhibitor in vitro . More importantly, miR-31 mimic decreased luciferase expression driven by the construct of CREG mRNA 3'-UTR in HEK293 cells, confirming CREG is a direct target of miR-31. Finally, knockdown of CREG in VSMCs, the effect of miR-31 inhibitor on SM α-actin expression is decreased. Conclusions: We conclude that miR-31 directly binds to CREG and modulate VSMC phenotype through its target gene CREG, and miR-31 can act as a more efficient biomarker of vascular diseases with pathological lesion based on VSMC phenotypic modulation.